Spatial Navigation Is Impaired in Elderly Patients With Cerebral Small Vessel Disease - Zhào, Hóngyi; Chi, Liyi; Zhang, Yanhai; Huang, Yonghua; Tian, Hongyan (Frontiers in Neurology, 2021)
Cerebral small vessel disease (SVD) refers to a heterogeneous group of pathological processes that result from damage to the small penetrating vessels in the brain. Spatial navigation, one of the most fundamental behaviors, has lately attracted considerable clinical interest. This study aimed to determine whether spatial navigation performance is impaired in elderly SVD patients. In total, 18 elderly patients with severe SVD, 40 elderly patients with non-severe SVD, and 41 age-matched healthy volunteers were classified according to the Fazekas scale. Spatial navigation was evaluated by Amunet (a computer-based analogy of Morris water maze software), and a mini-mental scale evaluation (MMSE), animal category verbal fluency test (VFT), clock drawing test (CDT), and trail making test (TMT) -B were also applied. Compared to healthy controls, severe SVD, rather than non-severe SVD patients, exhibited significantly worse performance on “allocentric + egocentric” (41.74 ± 29.10 vs. 31.50 ± 16.47 vs. 29.21 ± 19.03; p = 0.031). Furthermore, the different abilities of spatial navigation among groups reached a statistical level on allocentric subtests (46.93 ± 31.27 vs. 43.69 ± 23.95 vs. 28.56 ± 16.38; p = 0.003), but not on egocentric subtest (56.16 ± 39.85 vs. 56.00 ± 28.81 vs. 43.06 ± 25.07; p = 0.105). The linear regression analysis revealed that allocentric navigation deficit was significantly correlated with TMT-B (p = 0.000, standardized β = 0.342) and VFT (p = 0.016, standardized β = −0.873) performance in elderly SVD patients. These results elucidated that spatial navigation ability could be a manifestation of cognitive deficits in elderly patients with SVD.